FIP handbook on practical design examples of the design of concrete structures. (Thomas Telford, 1990)
This volume applies the FIP recommendations on practical design of reinforced and prestressed concrete structures to eight different worked examples of concrete structures, varying from simple beams to silo construction, flat slab design, incremental launching of bridge structures and other methods of bridge design and construction.